REFLECTIONS ON THE PRACTICE OF PHYSICS - Hon, Giora. ([S.l.])
1 online resource
Keywords: This monograph examines James Clerk Maxwell's contributions to electromagnetism to gain insight into the practice of science by focusing on scientific methodology as applied by scientists. First and foremost, this study is concerned with practices that are reflected in scientific texts and the ways scientists frame their research. The book is therefore about means and not ends.